Analysis of the Community Satisfaction Index on Public Services at the Sukaraja Sub-district Office, Seluma Regency - Retno Dwi Putri Nurfarida; Oni Yulianti; Yanto Effendi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The purpose of this study was to determine the Community Satisfaction Index of Public Services at the Sub-district Office of Sukaraja, Seluma Regency. The analytical method used is the Community Satisfaction Survey (SKM) based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 with 9 indicators, namely requirements, procedures, completion time, costs/tariffs, product specifications, types of services, competence of implementers, behavior implementer, handling complaints, suggestions and inputs, facilities and infrastructure. From the analysis of the community satisfaction index in the Community Satisfaction Survey (SKM) for public services at the Sukaraja District Head Office, Seluma Regency, it is 77.75 with service quality B with good criteria because it is in the range of conversion interval values ​​of 76.61 - 88.30.